The Contribution of Food Commodities to Inflation Rates: A Case Study of Agricultural Products in Region X - Apriyanto, Apriyanto; Safii, Muhammad (West Science Agro, 2025)
This study investigates the contribution of agricultural products to inflation rates in Region X, Indonesia, using a qualitative approach. Based on interviews with five farmers, the research identifies key factors influencing agricultural production and their link to inflationary pressures. Findings reveal that fluctuating input costs, climate variability, and supply chain inefficiencies significantly impact production levels and pricing mechanisms. Intermediaries play a dominant role in determining prices, creating a gap between farm-gate and market rates. Socio-economic vulnerabilities, including farmers' dual roles as producers and consumers, exacerbate the challenges posed by inflation. The study highlights the need for policy interventions, such as improved infrastructure, price stabilization mechanisms, and enhanced bargaining power for farmers, to address these issues. These findings contribute to a deeper understanding of inflation dynamics and the socio-economic challenges faced by smallholder farmers in Indonesia.